An allocation approach for external truck tasks appointment in automated container terminal. (January 2023) - He, Junliang; Zhang, Leijie; Deng, Yiyun; Yu, Hang; Huang, Mingzhong; Tan, Caimao
Abstract: Ports are the key connection of sea and land transportation. The coordination of container collection and distribution directly affect the handling efficiency of port in the entire supply chain. The optimization of tasks appointment for external trucks is crucial to improving the efficiency of container collection and distribution. The layout of the interchange points of external trucks are streamlined in automated container terminals where external trucks are commonly affected by the seaside operations. The traditional methods of external trucks assignment are inadequately applicable. In this paper an optimization model for the tasks appointment of external trucks is established for the joint optimization of external truck appointment and automated rail mounted gantry crane (ARMG) scheduling in the yard. Multiple objectives are generated including the balance of appointment among periods of time and between blocks. In this model the capacity constraints of the loading operations of external truck and moving operations of ARMGs between the seaside and landside are comprehensively considered. The model is solved by CPLEX and verified through sensitivity analysis. Different task appointment modes and various scenarios are compared and suggestions for selecting an optimization strategy are proposed. The experimental results show that the task appointment solutions effectively prevent the queuing of trucks, and balance the ARMG handling in automated container terminals, and herein the port efficiency is enhanced and the satisfaction of the carriers is promoted accordingly. It is also suggested that terminal managers should consider yard operations, operation capacity and the length of appointment period when considering the optimization of a task appointment schedule. While keeping optimize the appointment modes according to the operational conditions to improve the balance between the seaside and landside operations and reduce the idle of the ARMGs.